2020
DOI: 10.1155/2020/7409396
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Oral Analgesics and Pain Self-Efficacy Are Independent Predictors of the Quality of Life of Individuals with Rheumatoid Arthritis

Abstract: Objectives. This study investigated the relationship between quality of life (QOL) and several factors, including pain assessments, in patients with rheumatoid arthritis (RA). Methods. This cross-sectional, single-center study enrolled 85 patients with RA. The variables investigated included demographic characteristics, the 28-joint disease activity score with C-reactive protein (DAS28-CRP), painDETECT questionnaire (PDQ), pain self-efficacy questionnaire (PSEQ), and pain catastrophizing scale (PCS). QOL was m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 57 publications
1
15
0
Order By: Relevance
“…Individuals with high pain self-efficacy have stronger pain coping beliefs and are more likely to comply with health-related behaviors. 45 One study also found that the level of pain self-efficacy is negatively associated with anxiety and depression, which may also affect the QOL. 46 Finally, we detected positive correlations among social support, pain self-efficacy, MCS, and PCS.…”
mentioning
confidence: 99%
“…Individuals with high pain self-efficacy have stronger pain coping beliefs and are more likely to comply with health-related behaviors. 45 One study also found that the level of pain self-efficacy is negatively associated with anxiety and depression, which may also affect the QOL. 46 Finally, we detected positive correlations among social support, pain self-efficacy, MCS, and PCS.…”
mentioning
confidence: 99%
“…In fact, analgesic consumption may have masked the ocular pain symptoms, in exchange for a decrease in quality-of-life. Previous studies have shown that the use of oral analgesics is an independent predictor of lower scores of quality-of-life [20]. Using NSAIDs is associated with fatigue, anxiety, and depression in patients with rheumatoid arthritis [21].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the use of oral analgesics is an independent predictor of lower scores of quality-of-life. [20] Using NSAIDs is associated with fatigue, anxiety, and depression in patients with rheumatoid arthritis. [21] Based on our ndings, higher scores of ocular and facial pain, as well as photophobia before surgery herald higher odds of analgesic use after surgery.…”
Section: Discussionmentioning
confidence: 99%